(3edGc GdJChjd GdbGWY dPhi GdEdMGO hGdJYWjd aj JhLjg GdeJTGHg ef Bi GdJfRjds - (3CHi LYaQ CMeO Hf CMeO Hf EHQGgje GdeYQha Hf GdRHjQ GdKbai GdCfOdSj GdZQfGWis; (3GdGScGajs
(3ChdgG (B:s
(3GdMeO ddg GdPi GMJSHi ef UahI YHGOg s
(3GdfSNI HgG MhGTs
(3Yfi GdeDa ajg HGdJfHjg Ydi eG CZadg GdEScGai ai cJGH (B"(3OQI GdJfRjd hZQI GdJChjd(B"s
(3fSNI KGfjI s
(3JHUQI GdYfhGf (B:s
(3GSJOQGcs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs